Efeitos de cultivares de algodoeiro que expressam as proteínas Cry1Ac e Cry1F nos parâmetros biológicos de Chrysodeixis includens (Walker, 1857) (Lepidoptera: Noctuidae) - Viana, Daniela de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The cotton Gossypium hirsutum (L.) is a Malvaceae cultivated in various regions of Brazil and the world, due to the versatility of its production. The cotton is the main raw material for the textile industry, due to the characteristics and utility of its fiber; it is being also used for the production of oil and other sub products. The socioeconomic importance of cotton is located in the control of insect pests as a factor that brings the greatest costs in the production of this crop. The soybean looper, Chrysodeixis includens (Walker, 1857) (Lepidoptera: Noctuidae) of greater occurrence in the soybean crop until the last decade, is causing serious damages in the cotton regions. Among the main advances, in control of pests, could cite the availability of genetically modified cotton cultivars with gens coming of the bacteria Bacillus thuringiensis, where this transgenic plants express protein crystals with insecticide effects to control Lepidoptera pests that can become prejudicial to cotton. The events of cotton expressing Cry1Ac and, Cry1Ac and Cry1F proteins which are current and available tools to the management of this insect pest, in order to subsidize the integrated pest management. In this way, the objective of this study was to evaluate the effects of transgenic cotton cultivars expressing the Cry1Ac and, Cry1Ac and Cry1F proteins, in the biological parameters of C. includens and aiming at to determine the survivor of the species. This study was developed in the laboratory, in controlled conditions, it was used neonate larvae that were fed over the entirely larval phase with leaves of the transgenic cultivars, NuOPAL (Bollgard I®) and FM 975 (WideStrike®), and their respective conventional isolines, DeltaOPAL and FM 993. In each cultivar, the biological parameters observed were average duration and viability of larval phase, average duration and viability of the pupal phase, average ...

O algodão Gossypium hirsutum (L.) é uma Malvaceae cultivada em várias regiões do Brasil e do mundo, devido à versatilidade da sua produção, sendo a principal matéria-prima para a indústria têxtil, devido às características e utilidades de sua fibra, sendo utilizado também para a produção de óleo e outros subprodutos. A importância econômica do algodão atrela-se à questão do controle de insetos-praga como sendo um dos fatores que traz a maior parcela de custos na produção dessa cultura. A lagarta falsa-medideira, Chrysodeixis includens (Walker, 1857) (Lepidoptera: Noctuidae), de maior ocorrência na cultura da soja até a década passada, vem causando sérios danos nas regiões produtoras de algodão. Entre os principias avanços para o controle de pragas, pode-se citar a disponibilidade de cultivares de algodoeiro geneticamente modificadas com genes oriundos da bactéria Bacillus thuringiensis, onde essas plantas transgênicas expressam cristais proteicos com efeito inseticida, com a finalidade de controlar lepidópteros pragas que possam vir a ser prejudiciais à cultura. Os eventos de algodão Bt que expressam as proteínas Cry1Ac (Bollgard I®) e Cry1Ac mais Cry1F (WideStrike®) são ferramentas atuais e disponíveis para o manejo desse inseto-praga, afim de subsidiar o Manejo Integrado de Pragas. Dessa forma, o objetivo deste trabalho foi avaliar os efeitos de cultivares transgênicas de algodoeiro que expressam a proteína Cry1Ac e que expressam as proteínas Cry1Ac mais Cry1F, nos parâmetros biológicos de C. includens e visando determinar a sobrevivência da espécie. O estudo foi realizado em laboratório, sob condições controladas, utilizando lagartas neonatas que foram alimentadas durante toda a fase larval com folhas das cultivares transgênicas NuOPAL (Bollgard I®) e FM 975 (WideStrike®) e suas respectivas isolinhas convencionais, DeltaOPAL e FM 993. Em cada ...
Keywords: Algodão; Pragas agricolas - Controle biologico; Plantas cultivares; Lagarta; Bactérias; Agricultural pests